Multifunctional filter bag for tea boiling machine
By using a combination technology of pulling belt, binding ring, dynamic response substrate and molecular sieve functional units in the filter bag, the problems of tea component release regulation, mechanical strength and antibacterial performance are solved, and the precise control of tea quality and the extension of service life are achieved.
Patent Information
- Application Number
- CN202411962078.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-14
AI Technical Summary
The existing filter bags have shortcomings in tea ingredients release regulation, mechanical strength and durability, and hygiene performance, which are difficult to meet consumers' higher requirements for tea flavor, quality and convenience of use.
Using a technical solution of pulling belt, binding ring and dynamic response substrate and molecular sieve functional units, the pore size of the filter bag and the screening ability of the target molecules is regulated through temperature and pH response, the tea polyphenols and theanine are accurately released, and the mechanical strength and antibacterial properties are enhanced through nanofilters.
It realizes precise control of tea soup quality, significantly improves the quality control ability of tea soup, enhances the mechanical strength and antibacterial properties of filter bags, extends the service life, and meets the actual needs of higher standards.
Smart Images

Figure CN119606184A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of filter bags, in particular to a multifunctional filter bag for a tea maker. Background Art
[0002] Filter bags, as a common tool for boiling and brewing tea, have been widely used in daily life. Filter bags in the prior art mainly adopt physical filtering methods, which prevent tea debris from entering the tea soup by limiting the pore size of materials such as fiber mesh, polyester film or stainless steel mesh, thereby achieving a simple filtering effect. At the same time, in order to improve durability and convenience, some filter bags also try to use higher strength materials or add adsorbents to optimize the quality of tea soup. However, the functions of existing filter bags are mainly concentrated on basic filtering effects, which are difficult to meet consumers' higher requirements for tea flavor, quality and ease of use.
[0003] The filter bags in the prior art are single-layer structures, lacking a layered design or the addition of functional materials, which leads to a variety of problems in actual use. For example, the release of tea polyphenols, theanine, tannic acid and other ingredients in tea cannot be precisely regulated, which can easily lead to an imbalance in the taste of the tea soup; the static properties of the material cannot adapt to changes in different temperatures and pH values, making it difficult to achieve dynamic regulation; a single material is easily damaged or its performance degraded under long-term immersion at high temperatures, and its mechanical strength and durability are insufficient. In addition, filter bags that lack antibacterial functions are prone to breeding bacteria under high temperature and humid conditions, making it difficult to meet hygiene and safety requirements. Therefore, it is difficult for the prior art to achieve effective comprehensive optimization in terms of filtration performance, structural stability and safety of use, and it is urgently needed to be improved through innovative designs. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a multifunctional filter bag for a tea maker, which solves the problems in the prior art that the release of tea ingredients cannot be accurately controlled, the filter bag has insufficient mechanical strength and durability, and has poor hygienic performance.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: a multifunctional filter bag for a tea maker, comprising a bag body filter bag, a tightening ring filter bag is arranged on the upper part of the bag body filter bag, a drawstring belt filter bag is arranged inside the tightening ring filter bag, and the bag body filter bag is provided with a plurality of evenly distributed filter hole filter bags.
[0006] Preferably, the following components are also included: The dynamic response substrate is composed of N-isopropylacrylamide and polyacrylic acid and is formed by cross-linking with a cross-linking agent; Molecular sieve functional units, including mesoporous silica and cyclodextrin derivatives; performance-enhancing nanofillers, including graphene oxide and zinc oxide nanoparticles; Among them, the thickness of the dynamic response substrate is 50-100µm, the thickness of the molecular sieve functional unit is 30-50µm, and the thickness of the performance-enhancing nanofiller is 20-30µm.
[0007] Preferably, the mass of the N-isopropylacrylamide accounts for 40%-50% of the dynamic response substrate, and the mass of the polyacrylic acid accounts for 30%-40% of the dynamic response substrate.
[0008] Preferably, the cross-linking agent is N,N'-methylenebisacrylamide, and its mass accounts for 2% to 5% of the dynamic response substrate.
[0009] Preferably, the pore size of the mesoporous silica in the molecular sieve functional unit is in the range of 2-4 nm, and its mass accounts for 3% to 5% of the molecular sieve functional unit.
[0010] Preferably, the cyclodextrin derivative is β-cyclodextrin grafted with carboxyl groups, and its mass accounts for 2% to 4% of the molecular sieve functional unit.
[0011] Preferably, the mass of graphene oxide in the performance-enhancing nanofiller accounts for 1% to 2% of the performance-enhancing nanofiller, and the mass of zinc oxide nanoparticles accounts for 1% to 2% of the performance-enhancing nanofiller.
[0012] Preferably, the dynamic response substrate, the molecular sieve functional unit and the performance-enhancing nanofiller are composited by multiple coating processes, and the number of coating times is 2-3 times.
[0013] Preferably, the bag body of the filter bag is made of a composite film, which is cut into a size of 8 cm×12 cm by laser cutting and packaged by heat sealing technology, with a heat sealing temperature of 100-120° C. and a heat sealing time of 3 to 5 seconds.
[0014] Preferably, the three-layer structure of the composite membrane is: a dynamic response substrate layer, a molecular sieve functional unit layer and a performance-enhancing nanofiller layer.
[0015] The present invention provides a multifunctional filter bag for a tea maker, which has the following beneficial effects: 1. The present invention uses a technical solution of a drawstring, a restraining ring, a dynamic response substrate and a molecular sieve functional unit, and adjusts the pore size of the filter bag and the screening ability of the target molecule through temperature and pH response, thereby achieving the effect of accurately releasing tea polyphenols and theanine. Compared with the single physical filtration solution in the prior art, it solves the problem of uneven release of tea ingredients and waste of some nutrients, and significantly improves the quality control ability of tea soup.
[0016] 2. The present invention realizes the dual functions of molecular recognition and screening by utilizing the synergistic effect of mesoporous silica and cyclodextrin derivatives, and achieves the technical effect of effectively blocking undesirable components such as tannic acid and tea saponin. Compared with the permeability problem of traditional filter bags that cannot distinguish different molecules, the present invention overcomes the deficiency of causing excessive bitterness of tea soup, and provides an innovative path for preparing high-quality tea soup with a pure taste.
[0017] 3. The present invention not only enhances the mechanical strength of the filter bag by introducing graphene oxide and zinc oxide nanoparticles, but also significantly improves its stability and antibacterial properties in a high-temperature tea-making environment. Compared with the safety issues in the prior art caused by poor heat resistance of materials and microbial contamination, the present invention provides a more durable and hygienic multifunctional filter bag, which effectively extends the service life and meets higher standards of actual needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A perspective view of the present invention; Figure 2 It is a schematic diagram of the bag body structure of the present invention.
[0019] Among them, 1. tightening ring; 2. drawstring; 3. filter hole; 4. bag body. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Please see attached Figure 1 The embodiment of the present invention provides a multifunctional filter bag for a tea maker, comprising a bag body 4, a tightening ring 1 is arranged on the upper part of the bag body 4, a drawstring 2 is arranged inside the tightening ring 1, and a plurality of evenly distributed filter holes 3 are opened on the bag body 4; Composition and preparation of dynamic response substrate The dynamic response substrate is formed by cross-linking poly(N-isopropylacrylamide) (PNIPAM) and polyacrylic acid (PAA) through a cross-linking agent. Among them, PNIPAM is a typical thermosensitive material with a critical solution temperature (LCST) of about 32°C. Below LCST, the PNIPAM molecular chain is in a hydrophilic swelling state with a larger pore size; above LCST, its molecular chain undergoes hydrophobic collapse and the pore size decreases rapidly. PAA is a pH-sensitive polymer that undergoes ionization or deionization reactions in an acidic or alkaline environment, and its chain structure swells or shrinks with changes in pH. This dual response mechanism enables the substrate to dynamically adjust the pore size and permeability of the filter bag under different tea-making conditions.
[0022] The temperature response of PNIPAM is determined by the competitive effect between the hydrophobic isopropyl group and the hydrophilic amide group in its molecular chain. When the temperature rises above the LCST, the hydrophobic effect of the isopropyl group becomes dominant, causing the molecular chain to collapse and the filtration pore size to decrease, thereby blocking the excessive release of macromolecular substances (such as tannic acid).
[0023] PAA is ionized under alkaline conditions, and the electrostatic repulsion between charges allows its chain segments to fully expand, thereby increasing the pore size; it is deionized under acidic conditions, and the pore size decreases, thereby regulating the release of specific ingredients (such as tea saponin).
[0024] Preparation method: Formula ratio: PNIPAM accounts for 40% to 50% of the total mass of the dynamic response substrate; PAA accounts for 30% to 40%; and the cross-linking agent N,N'-methylenebisacrylamide (MBAA) accounts for 2% to 5%.
[0025] Preparation process: At 70-80°C, PNIPAM was dissolved in deionized water with a stirring rate of 300-500 rpm to form a uniform solution; then the PAA solution was slowly added and stirring was continued for 1-2 hours to form a mixed solution.
[0026] MBAA crosslinking agent was added, and ammonium persulfate (APS) was added as an initiator at 50-60°C for a reaction time of 0.5-1 hour to complete the crosslinking reaction and obtain a thermosensitive and pH-sensitive dual-functional substrate.
[0027] Composition and modification of molecular sieve functional units The molecular sieve functional unit is composed of mesoporous silica (MCM-41) and cyclodextrin derivative (β-cyclodextrin). Mesoporous silica is an inorganic material with uniform pore size ranging from 2-4nm, which can effectively block larger tea components (such as tea saponins and tannic acid) through size sieving effect. Cyclodextrin is a host-guest recognition molecule with hydrophilic and hydrophobic partitions in its structure, which can selectively capture target molecules (such as tea polyphenols and theanine).
[0028] Preparation method: Formula ratio: mesoporous silica accounts for 3% to 5% of the total mass of the molecular sieve unit; cyclodextrin derivatives account for 2% to 4%.
[0029] Preparation process: MCM-41 was dispersed in anhydrous ethanol and treated by ultrasonic dispersion (power 150-200W) for 15-30 minutes to prepare a uniform suspension.
[0030] β-cyclodextrin is modified by carboxyl groups: β-cyclodextrin is mixed with MCM-41 suspension under the condition that the pH value is adjusted to 6.0-7.0, stirred for 2-4 hours, and the temperature is controlled at 50-60°C. The modification is completed by covalent bonding between silanol and carboxyl groups.
[0031] Nanofillers for enhanced performance The performance-enhancing nanofiller consists of graphene oxide (GO) and zinc oxide (ZnO) nanoparticles. GO, as a two-dimensional nanomaterial, has high strength and high adsorption capacity. Its surface contains functional groups such as carboxyl and hydroxyl groups, which can form non-covalent bonds with polyphenols in tea, thereby improving the selective adsorption performance of the filter bag. ZnO has good antibacterial and thermal stability, which can enhance the mechanical properties of the filter bag and its safety in high temperature environments.
[0032] Preparation method: Formula ratio: GO accounts for 1% to 2% of the total mass of nanofiller; ZnO accounts for 1% to 2%.
[0033] Preparation process: GO was dissolved in deionized water and treated by ultrasonic dispersion (power 150-250 W) for 15-20 min to form a homogeneous solution.
[0034] Add ZnO nanoparticles to the GO dispersion, stir at a rate of 300-500 rpm, control the temperature at 50-60°C, and mix for 0.5-1 hour to form a stable composite filler.
[0035] Preparation of composite film and bag packaging The dynamic response substrate, molecular sieve functional unit and performance-enhancing nanofiller are coated and compounded multiple times to form a three-layer membrane structure, and finally the bag body is formed through cutting and heat sealing processes.
[0036] Coating composite process: First, the dynamic response substrate is evenly coated on the surface of the glass plate, the coating thickness is controlled to be 50-100µm, and it is dried at 60-80°C for 2-4 hours.
[0037] The molecular sieve functional unit solution is evenly coated on the surface of the substrate with a coating thickness of 30-50µm and cured at 70-90°C for 1-3 hours.
[0038] The last layer of nanofiller is sprayed, with a coating thickness of 20-30µm, and dried at 100-120°C for 1-2 hours to form a composite film.
[0039] Bag packaging process: The composite film was cut into a size of 8 cm × 12 cm using laser cutting technology and packaged into bags using heat sealing technology (temperature 100-120°C, time 3-5 seconds).
[0040] Example 1: Preparation and performance verification of dynamic response substrate Material dissolution Take 4 g of poly(N-isopropylacrylamide) (PNIPAM) and 3 g of polyacrylic acid (PAA) and add them to 80 mL of deionized water. Heat the solution to 75 °C and set the stirring speed to 400 rpm for 1 hour until they are completely dissolved to form a uniform transparent solution.
[0041] Cross-linking reaction 0.3 g of N,N'-methylenebisacrylamide (MBAA) was added to the solution as a crosslinker, followed by a dropwise addition of 0.2 g of ammonium persulfate (APS) solution (prepared at a concentration of 5%), and the reaction temperature was maintained at 60°C. The reaction time was controlled at 40 minutes until the solution viscosity increased significantly.
[0042] Substrate film formation The mixed solution was evenly coated on a glass substrate, and a scraper was used to control the coating thickness to 80 µm. The glass substrate was placed in an oven at 70°C and dried for 2 hours to form a flexible film. Subsequently, the mold was removed to obtain a dynamic response substrate film.
[0043] Performance Testing The pore size change of the substrate film was measured at 30°C and 50°C and detected by dynamic light scattering. The results showed that the pore size range was 45nm at low temperature and decreased to 18nm at high temperature, confirming its excellent temperature response performance.
[0044] Example 2: Preparation and modification of molecular sieve units Mesoporous silica dispersion Take 2 g of mesoporous silica (MCM-41), add it to 50 mL of anhydrous ethanol, and disperse it ultrasonically for 15 minutes with the power set to 180 W to ensure uniform particle distribution.
[0045] Cyclodextrin modification Prepare cyclodextrin modified solution: Take 1g of β-cyclodextrin, add it to 40mL of deionized water, and adjust the solution pH to 6.5. Then mix the above silica dispersion with the cyclodextrin solution, place it in a 50°C water bath and stir for 3 hours until the reaction is complete.
[0046] Functional unit preparation The reaction mixture was centrifuged to remove unreacted cyclodextrin. The precipitate was washed with deionized water for three times, dried and ground into powder to obtain cyclodextrin-modified mesoporous silica.
[0047] Screening capacity test The prepared functional units were mixed with tea components in the solution, and the screening effect was tested in a liquid chromatograph. The results showed that the content of tannic acid was reduced by 50%, while the content of tea polyphenols remained above 90%, proving its excellent selective screening performance.
[0048] Example 3: Preparation of nanofillers and composite membranes with enhanced performance Nanofiller dissolution Take 0.5g of graphene oxide (GO) and add it to 30mL of deionized water. Ultrasonic dispersion is performed for 20 minutes with the power set to 200W. Then 0.3g of zinc oxide (ZnO) nanoparticles is added and stirring is continued for 30 minutes with the temperature controlled at 50°C to form a uniform dispersion.
[0049] Preparation of composite membranes Substrate coating: The dynamic response substrate solution prepared in Example 1 was coated on a glass plate to form a substrate film after drying with a thickness of about 80 μm.
[0050] Molecular sieve unit coating: The molecular sieve functional unit prepared in Example 2 was uniformly coated on the substrate film, with a thickness of 40 μm. The drying condition was 75° C. and the drying time was 1 hour.
[0051] Enhanced coating spraying: The graphene oxide-zinc oxide dispersion was sprayed on the membrane surface with a thickness of 20 µm. It was then dried at 100°C for 2 hours to form the final composite membrane.
[0052] Antibacterial performance test The composite film was exposed to a bacterial suspension environment and the antibacterial effect was tested after 24 hours of incubation. The results showed that the antibacterial rate reached 95%, indicating that the zinc oxide nanoparticles gave the material good antibacterial properties.
[0053] Example 4: Preparation of composite filter bag and component release test Film cutting and packaging The composite film prepared in Example 3 was cut into bags of 8 cm×12 cm using laser cutting technology. The edge of the bag was placed in a heat sealer, the temperature was set to 110° C., the heat sealing time was 3 seconds, and the packaging was completed.
[0054] Filter bag performance test The tea sample (3 g) was added to a filter bag and boiled in a tea maker for 3 minutes. The concentrations of polyphenols, theanine and tannic acid in the tea soup were then tested by liquid chromatography. The test results showed: The release of tea polyphenols increased by 35%, tannic acid decreased by 40%, and theanine retention rate reached 92%.
[0055] This shows that filter bags have significant advantages in ingredient screening and release control.
[0056] Example 5: Dynamic response and long-term stability test Preparation and Assembly The bag was prepared using the composite film of Example 3. The bag had a size of 10 cm×15 cm and contained 5 g of tea leaves.
[0057] Dynamic response test The tea brewing test was conducted under different temperature conditions (30°C, 40°C, 50°C), and each test lasted for 5 minutes. The changes in the content of tea polyphenols and tannic acid in the tea soup were detected, and the results showed: As the temperature increases, the tannic acid content decreases significantly (from 50 mg / L to 20 mg / L), and the release of tea polyphenols is stable, indicating that the dynamic response substrate has a significant control effect on temperature changes.
[0058] Stability test The filter bag was placed in a high temperature (100°C) water bath for 1 hour to observe whether the bag body had cracks or performance degradation. The results showed that the bag body had no obvious changes and the material structure remained stable.
[0059] Comparative Example 1: No bifunctional polymer is used in the dynamic response substrate (corresponding to Example 1) Material dissolution Take 7 g of poly (N-isopropylacrylamide) (PNIPAM), add it to 80 mL of deionized water, stir and heat to 75 ° C, stir at 400 rpm, and take 1 hour to dissolve completely.
[0060] Cross-linking reaction 0.3 g of N,N'-methylenebisacrylamide (MBAA) was added to the solution as a cross-linking agent, followed by dropwise addition of 0.2 g of ammonium persulfate (APS) solution, the temperature was maintained at 60 °C, and the reaction time was 40 min.
[0061] Substrate film formation The above solution was evenly coated on a glass substrate, the coating thickness was controlled to be 80 µm, and the film was dried at 70°C for 2 hours, and then demolded to obtain a single temperature-responsive substrate film.
[0062] The difference from Example 1 is that polyacrylic acid (PAA) is not added, resulting in the substrate lacking pH response characteristics and only having temperature response function.
[0063] Comparative Example 2: No cyclodextrin modification was performed in the molecular sieve functional unit (corresponding to Example 2) Mesoporous silica dispersion Take 2 g of mesoporous silica (MCM-41), add it to 50 mL of anhydrous ethanol, and disperse it ultrasonically for 15 min at a power of 180 W to ensure that the particles are evenly distributed.
[0064] Functional unit preparation The dispersed MCM-41 particles were directly centrifuged and dried without further modification to obtain unmodified mesoporous silica powder.
[0065] The difference from Example 2 is that cyclodextrin is not used to modify the mesoporous silica, and the host-guest recognition function is lacking.
[0066] Comparative Example 3: No nanofiller is used (corresponding to Example 3) Coating of dynamically responsive substrates The dynamic response substrate solution prepared in Example 1 was evenly coated on a glass substrate, and after drying, a substrate film with a thickness of 80 μm was formed.
[0067] Coating of molecular sieve functional units The molecular sieve functional unit solution prepared in Example 2 was uniformly coated on the substrate film with a thickness of 40 μm. The drying condition was 75° C. and the drying time was 1 hour.
[0068] The difference from Example 3 is that graphene oxide and zinc oxide nanoparticles are not sprayed as a reinforcing coating, and the mechanical strength and antibacterial performance enhancement functions of nanofillers are lacking.
[0069] Comparative Example 4: Dual dynamic response mechanism not adopted (corresponding to Example 1 and Example 3) Substrate preparation Only 3 g of polyacrylic acid (PAA) was used as the dynamic response material, added to 80 mL of deionized water, stirred and heated to 75 ° C for 1 hour. Then 0.3 g of N, N'-methylenebisacrylamide (MBAA) and 0.2 g of ammonium persulfate (APS) were added, the temperature was maintained at 60 ° C, and the reaction was carried out for 40 minutes.
[0070] Composite membrane preparation Substrate coating: The above PAA solution was evenly coated on a glass plate to form a single-layer film with a thickness of 80 µm.
[0071] Molecular sieve unit coating: The molecular sieve unit prepared in Example 2 is coated on the substrate membrane with a thickness of 40 μm.
[0072] Reinforced coating spraying: Spray the nanofiller in Example 3, drying condition is 100° C., time is 2 hours.
[0073] The difference from Example 1 and Example 3 is that the substrate only has a pH response function, the temperature response characteristics of PNIPAM are not introduced, and the dual response regulation capability is lacking.
[0074] Comparative Example 5: No multi-layer composite structure is used (corresponding to Example 4) Preparation of single-layer substrate film The dynamic response substrate solution prepared in Example 1 was evenly coated on a glass substrate to form a single-layer substrate film with a thickness of 80 μm.
[0075] Bag packaging The single-layer substrate film was cut into bags of 8 cm × 12 cm in size and sealed by a heat sealer with the temperature set at 110°C and the heat sealing time set for 3 seconds.
[0076] The difference from Example 4 is that the molecular sieve functional unit and the performance-enhancing coating are not introduced, only a single-layer substrate membrane is used, and the functionality and strength optimization of the multi-layer composite structure are lacking.
[0077] Comparative Example 6: Improper heat sealing parameters (corresponding to Example 4) Composite membrane preparation The composite membrane was prepared according to the method of Example 3, including dynamic response substrate coating, molecular sieve functional unit coating and nanofiller enhanced coating.
[0078] Bag packaging The composite film was cut into a bag size of 8 cm × 12 cm, but the heat sealing temperature was set to 90°C and the heat sealing time was 2 seconds to complete the packaging.
[0079] Difference from Example 4: The heat sealing temperature and time are not optimal, which may result in insufficient sealing and stability of the edge of the bag.
[0080] Experiment 1: Dynamic response performance test Experimental Description Purpose The pore size regulation capability of the dynamic response substrate of Example 1 under different temperature and pH conditions was verified, demonstrating the superiority of its dual-functional dynamic response characteristics over those of Comparative Examples 1 and 4.
[0081] Experimental procedures Sample preparation Example 1 Sample: Dual-functional dynamic response substrate film (PNIPAM+PAA).
[0082] Comparative Example 1 sample: single-functional temperature-responsive substrate film (PNIPAM only).
[0083] Comparative Example 4 sample: single-functional pH-responsive substrate membrane (PAA only).
[0084] Temperature response test The three groups of samples were immersed in deionized water at 30°C, 40°C and 50°C respectively for 10 minutes, and then samples were taken for pore size testing.
[0085] Dynamic light scattering (DLS) was used to detect the average pore size of each sample and record the data.
[0086] pH response test Buffer solutions of pH 3.0, 7.0, and 9.0 were prepared, and the three groups of samples were immersed for 15 minutes, and then the changes in pore size were tested.
[0087] Each group of samples was tested 3 times under the corresponding pH conditions, and the average value was taken.
[0088] Experimental setup Temperature range: 30°C to 50°C, step 10°C.
[0089] pH range: 3.0, 7.0, 9.0.
[0090] Each test point was tested 3 times to ensure the data accuracy.
[0091] Experimental data Table Name: Sample No. Temperature (30°C) Temperature (40°C) Temperature (50°C) pH 3.0 pH7.0 pH 9.0 Example 1 44 35 19 15 38 56 Comparative Example 1 47 38 21 46 47 48 Comparative Example 4 52 53 51 16 28 51 The core of dynamic response materials lies in the dual sensitivity. In the experiment, when the temperature conditions change in Example 1, the volatility of the pore size is significantly higher than that in Comparative Example 1. This change is not a simple swelling or shrinkage, but comes from the hydrophilic and hydrophobic transformation of the PNIPAM chain segments. After heating, the molecular chain collapses and the pore size rapidly decreases, preventing unnecessary large molecules from passing through. However, a single PNIPAM (Comparative Example 1) can only respond to temperature and cannot regulate the screening effect in a pH environment.
[0092] Interestingly, under pH conditions, Example 1 exhibits sensitivity to acid-base changes, which is the unique contribution of PAA. At low pH, PAA deionizes and the molecular chain compresses, keeping the pore size small; while at high pH, the ionization of PAA generates a repulsive force, which significantly increases the pore size. However, Comparative Example 4 is more limited due to the lack of temperature response, and only exhibits a single pore size adjustment behavior under pH changes.
[0093] From a mechanistic perspective, the bifunctional polymers form a synergistic effect in structure. The combination of PNIPAM and PAA not only gives the substrate multiple responsiveness, but also regulates the interaction between molecular chains through the internal network. The significant difference in pore size changes in the experiment is a direct reflection of this feature. Different from the limitations of single-functional responsive materials in existing technologies, this synergistic mechanism provides new possibilities for multi-scenario applications.
[0094] Experiment 2: Component screening performance test Experimental Description Purpose By testing the efficiency of Example 2 and Comparative Example 2 in screening tea components, the ability of cyclodextrin-modified mesoporous silica to capture target molecules was verified, reflecting the screening advantage of the present invention.
[0095] Experimental procedures Sample preparation Example 2: Cyclodextrin-modified mesoporous silica (MCM-41).
[0096] Comparative Example 2: Unmodified mesoporous silica.
[0097] Tea extract preparation Weigh 3 g of tea powder, add it into 100 mL of deionized water, boil it for 5 minutes, cool it down and filter it to obtain a simulated tea extract.
[0098] Screening experiment 0.5 g of the samples of Example 2 and Comparative Example 2 were added to 10 mL of the extract respectively and allowed to stand at room temperature for 30 minutes.
[0099] After standing, samples were taken and the concentrations of tea polyphenols, theanine and tannic acid were determined using high performance liquid chromatography (HPLC).
[0100] Experimental setup Tea extract concentration: 30g / L.
[0101] Sample addition amount: 0.5g / 10mL extract.
[0102] Standing time: 30 minutes.
[0103] Experimental data Table Name: Sample No. Tea polyphenols (mg / L) Theanine (mg / L) Tannic acid (mg / L) Example 2 78 42 18 Comparative Example 2 62 35 37 In the screening experiment, cyclodextrin-modified MCM-41 showed excellent selectivity. The concentrations of tea polyphenols and theanine were significantly higher than those of the unmodified samples. This is not simply physical adsorption, but is derived from the host-guest chemical effect of cyclodextrin. Its hydrophobic cavity provides a "locking point" for the target molecules, achieving efficient capture and sustained release. At the same time, the content of tannic acid was greatly reduced, indicating that the modified molecular sieve has enhanced its barrier ability to non-target macromolecules during the screening process.
[0104] The high tannic acid content of the unmodified sample indicates that its screening mechanism relies solely on pore size. This simple physical screening cannot distinguish the chemical properties of the molecules, resulting in a more significant impact on the quality of the tea. Example 2 obviously overcomes this problem through chemical modification.
[0105] From the perspective of molecular mechanism, the addition of cyclodextrin gives mesoporous silica chemical selectivity. The distribution of hydrophobic and hydrophilic regions not only limits the screening of molecular size, but also extends to the selective bonding of chemical bonds. This dual mechanism gives the present invention an irreplaceable technical advantage in actual tea applications.
[0106] Experiment 3: Antibacterial performance test Experimental Description Purpose By testing the antibacterial properties of the samples of Example 3 and Comparative Example 3, the enhanced effect of the nanofillers (zinc oxide and graphene oxide) on bacterial inhibition was verified, highlighting the advantages of the present invention in terms of hygienic safety.
[0107] Experimental procedures Sample preparation Example 3 Sample: a composite film containing zinc oxide and graphene oxide.
[0108] Comparative Example 3 sample: a composite film without nanofiller.
[0109] Bacterial liquid preparation Staphylococcus aureus (ATCC6538) and Escherichia coli (ATCC8739) were selected as test strains.
[0110] After the strain was cultured in nutrient agar for 24 hours, it was diluted with sterile saline to a bacterial concentration of 10 6 CFU / mL.
[0111] Antimicrobial testing The sample was cut into small pieces of 2 cm×2 cm and placed in a sterile culture dish.
[0112] 100 µL of bacterial solution was added to each sample and cultured in a 37°C constant temperature incubator for 24 hours.
[0113] After incubation, the sample surface was washed with sterile phosphate buffer, and the dilution was used to count the number of colonies by the agar plate method.
[0114] Experimental setup Test strains: Staphylococcus aureus, Escherichia coli.
[0115] Amount of bacterial solution added: 100µL / sample.
[0116] Incubation temperature: 37°C.
[0117] Cultivation time: 24 hours.
[0118] Experimental data Table Name: Sample No. strain Initial bacterial concentration (CFU / mL) Bacterial concentration after culture (CFU / mL) Antibacterial rate (%) Example 3 Staphylococcus aureus <![CDATA[10 6 ]]> 1.2×10³ 99.88 Example 3 Escherichia coli <![CDATA[10 6 ]]> 2.8×10³ 99.72 Comparative Example 3 Staphylococcus aureus <![CDATA[10 6 ]]> <![CDATA[1.6×10 5 ]]> 84 Comparative Example 3 Escherichia coli <![CDATA[10 6 ]]> <![CDATA[2.4×10 5 ]]> 76 The difference in antibacterial properties is vividly demonstrated here. The sample in Example 3 can almost completely inhibit bacterial growth, with an inhibition rate of nearly 99% for both Staphylococcus aureus and Escherichia coli. This ability is not achieved by a single component, but is the result of the combined action of zinc oxide and graphene oxide. The Zn²⁺ ions released by zinc oxide damage the bacterial cell membrane, while the two-dimensional structure of graphene oxide provides a physical barrier for the cells. The dual effect is particularly powerful.
[0119] Comparative Example 3 is completely different. It only relies on the physical properties of the substrate to inhibit bacteria, and the effect is very limited. It can be clearly seen from the data that the number of colonies is still high, especially in E. coli, where the inhibition rate is only 76%. This proves that the introduction of nanofillers is a key step in improving the antibacterial effect, and this step is obviously missing in the comparative example.
[0120] The mechanism of this antibacterial ability is inseparable from the combination of chemistry and physics. Zn²⁺ is a destroyer at the chemical level, directly interfering with bacterial metabolism, while graphene oxide is the creator of a physical barrier to prevent further spread of bacteria. The synergistic effect of this dual approach is precisely the advantage of Example 3 in practical applications. In contrast, the antibacterial ability of Comparative Example 3 can only be limited to the inert properties of the material itself, and cannot match the present invention in terms of efficiency or mechanism.
[0121] Experiment 4: Actual performance test of filter bags Experimental Description Purpose Through the actual tea-making scenario, the differences in ingredient release control, sealing and overall performance of the filter bags of Example 4 and Comparative Example 6 were compared to verify the importance of composite structure and optimized process.
[0122] Experimental procedures Sample preparation Example 4 Sample: Composite membrane structure filter bag, containing a dynamic response substrate, a molecular sieve functional unit and an enhanced nano-coating, with heat sealing parameters of 110°C and a time of 3 seconds.
[0123] Comparative Example 6 sample: prepared with the same material, but the heat sealing parameters are 90°C and the time is 2 seconds, and the sealing is weaker.
[0124] Tea preparation and tea brewing operations 3 g of evenly ground tea sample was placed in each set of filter bags, which were sealed and placed in a tea-making machine.
[0125] Add 300 mL of deionized water and set the tea brewing time to 3 minutes.
[0126] Test content Ingredient detection: After brewing the tea, take the tea soup and use high performance liquid chromatography (HPLC) to analyze the concentration of tea polyphenols, theanine and tannic acid.
[0127] Sealing observation: Check whether the filter bag leaks tea and record any sealing problems.
[0128] Bag integrity test: Take out the bag and observe whether there are cracks or damages in the bag after boiling tea at high temperature.
[0129] Experimental setup Tea weight: 3g / bag.
[0130] Water volume: 300mL.
[0131] Brewing time: 3 minutes.
[0132] Each group of samples was repeated 3 times and the average value was taken.
[0133] Experimental data Table Name: Sample No. Tea polyphenols (mg / L) Theanine (mg / L) Tannic acid (mg / L) Is tea leaking? Bag status Example 4 85 40 16 no intact Example 4 86 42 17 no intact Example 4 84 39 15 no intact Comparative Example 6 70 31 30 yes Edge cracking Comparative Example 6 72 30 28 yes Edge cracking Comparative Example 6 69 32 31 yes Edge cracking The process of brewing tea is a real test of the performance of the filter bag. The filter bag of Example 4 performed very reliably, and both the sealing and bag integrity withstood the test of high temperature and liquid immersion. In terms of ingredient release, the concentrations of tea polyphenols and theanine were significantly higher than those of Comparative Example 6. This is not only due to the improvement of heat sealing technology, but also the stability provided by the composite structure. The cracking phenomenon of the bag edge of Comparative Example 6 almost doomed its limitations in practical application from the beginning.
[0134] From a mechanistic point of view, the layered design of the composite structure is the key. The dynamic response substrate controls the pore size at high temperature and accurately screens the target molecules, while the molecular sieve functional unit effectively captures the important components in tea while screening macromolecules. Without these synergistic mechanisms, such an effect cannot be achieved by the strength of the material itself.
[0135] The difference is particularly obvious in the comparison of heat sealing processes. In Comparative Example 6, the edge is not fully sealed due to the packaging temperature being too low, and leakage of tea debris becomes an inevitable problem. However, in Example 4, the heat sealing temperature and time are strictly controlled, so that the bag body maintains its overall integrity under high temperature conditions. This optimization of detail processing directly reflects the technical advantages.
[0136] Experiment 5: Long-term use stability test Experimental Description Purpose The stability of the filter bags of Example 4 and Comparative Example 5 was compared by a long-term tea-boiling test to verify the effects of the multi-layer composite structure and process optimization on durability and structural integrity.
[0137] Experimental procedures Sample preparation Example 4 Sample: three-layer composite membrane filter bag (dynamic response substrate + molecular sieve functional unit + nanofiller coating).
[0138] Comparative Example 5 sample: single-layer substrate membrane filter bag, without composite membrane structure.
[0139] Tea brewing experiment Each set of filter bags was filled with 3 g of tea leaves, sealed and placed in a tea maker, and 300 mL of deionized water was added.
[0140] Set the tea brewing time to 60 minutes, and record the bag status 6 times (once every 10 minutes) to observe whether there are any cracks, damage or tea leakage.
[0141] Performance Testing After brewing the tea, take out the bag and use a tensile testing machine to test the tensile strength of the bag to evaluate whether the mechanical properties have decreased.
[0142] Visually inspect the tea soup and record whether any tea leaves have leaked out.
[0143] Experimental setup Tea weight: 3g / bag.
[0144] Water volume: 300mL.
[0145] Tea brewing time: 60 minutes, recorded in 10-minute groups.
[0146] Test environment: constant temperature room, 25°C.
[0147] Experimental data Table Name: Sample No. Time (10 minutes) Bag status Tensile strength (MPa) Is tea leaking? Example 4 10 minutes intact 42.1 no Example 4 20 minutes intact 41.8 no Example 4 30 minutes intact 41.3 no Example 4 40 minutes intact 40.9 no Example 4 50 minutes intact 40.5 no Example 4 60 minutes intact 40.1 no Comparative Example 5 10 minutes intact 28.4 no Comparative Example 5 20 minutes Cracked edge 27.5 yes Comparative Example 5 30 minutes Crack intensification 25.8 yes Comparative Example 5 40 minutes Edge damage 23.2 yes Comparative Example 5 50 minutes Large area damage 21 yes Comparative Example 5 60 minutes Overall rupture 19.5 yes The stability of the filter bag during long-term use directly determines its practicality. In the experiment, the filter bag of Example 4 remained intact without any signs of leakage or damage. The root of this performance lies in the synergy of the multi-layer composite structure, especially the combination of the dynamic response substrate and the nanofiller, which provides strength and fatigue resistance. In contrast, in Example 5, due to the lack of molecular sieve layer and coating protection, the single-layer substrate can maintain strength in a short period of time, but cracking and damage become inevitable results over time.
[0148] From a mechanistic point of view, the dynamic response substrate in Example 4 stabilizes the structural stress through the regulation of the molecular chain in the hot water environment, avoiding tearing caused by local stress concentration. The molecular sieve functional unit disperses the stress on the bag to a certain extent, making the overall structure more uniform. However, after the single-layer substrate of Comparative Example 5 is stressed, the molecular chain cannot be effectively regulated, and the accumulated stress eventually leads to edge damage or even overall tearing.
[0149] The addition of nanofillers further enhances the mechanical properties of the bag under high temperature conditions. Zinc oxide and graphene oxide not only improve the strength of the material, but also enhance the overall toughness through interaction with the substrate. This advantage is particularly evident under the condition of long-term tea brewing. Comparative Example 5 completely exposes the defects of traditional single-layer materials, with a significant decrease in both tensile strength and durability.
[0150] The performance advantages of the filter bag in Example 4, combined with the mechanism analysis, can be attributed to the dual improvement of material innovation and process optimization. The design of the multi-layer composite membrane achieves coordination and unity from the molecular level to the macroscopic performance, which is an effect that is difficult to achieve in the existing technology.
[0151] Experiment 6: High temperature durability test Experimental Description Purpose The durability of Example 4 and Comparative Example 5 under high temperature and long-term immersion conditions was tested to verify the significant improvement in material performance stability of the multi-layer composite structure and the dynamic response substrate, and to evaluate the bag integrity and strength changes.
[0152] Experimental procedures Sample preparation Example 4 Sample: Multilayer composite membrane structure filter bag (dynamic response substrate + molecular sieve functional unit + nanofiller coating).
[0153] Comparative Example 5 sample: single-layer substrate membrane filter bag, without multi-layer composite structure.
[0154] Test Operation Each set of filter bags was filled with 3 g of tea leaves, sealed and then soaked in 100°C boiling water for 1 hour.
[0155] During the soaking process, observe the appearance of the bag every 10 minutes and record whether there are any cracks, damage or tea leakage.
[0156] After the soaking is completed, the bag is taken out and dried, and the tensile strength of the bag is measured using a tensile testing machine, and the change range is recorded.
[0157] Performance Testing Appearance inspection: record whether the bag remains intact and whether tea leakage occurs.
[0158] Mechanical properties test: After sampling, the tensile strength of the bag is measured and compared with the initial strength to evaluate the strength retention rate under high temperature conditions.
[0159] Experimental setup Tea weight: 3g / bag.
[0160] Soaking time: 1 hour.
[0161] Recording interval: record the bag status every 10 minutes.
[0162] Water temperature: 100°C (boiling water environment).
[0163] Experimental data Table Name: Sample No. Time (10 minutes) Bag status Initial tensile strength (MPa) Final tensile strength (MPa) Strength retention rate (%) Example 4 10 minutes intact 42.3 41.9 99 Example 4 20 minutes intact 42.3 41.5 98.1 Example 4 30 minutes intact 42.3 41 97 Example 4 40 minutes intact 42.3 40.5 95.7 Example 4 50 minutes intact 42.3 40.2 95 Example 4 60 minutes intact 42.3 40 94.5 Comparative Example 5 10 minutes intact 28.7 26.4 91.9 Comparative Example 5 20 minutes Edge cracking 28.7 22.6 78.7 Comparative Example 5 30 minutes Edge damage 28.7 19.3 67.2 Comparative Example 5 40 minutes Edge tearing 28.7 16.1 56.1 Comparative Example 5 50 minutes Bag rupture 28.7 13.5 47 Comparative Example 5 60 minutes Overall rupture 28.7 10.9 37.9 The high-temperature immersion in the experiment is an extreme challenge to the material performance. Example 4 shows excellent stability, and the bag body remains intact throughout the whole process without any cracks or damage. The realization of this performance is due to the synergistic effect of the multilayer structure of the composite film. The dynamic response substrate adjusts stress through molecular chains at high temperatures to avoid structural damage caused by stress concentration. At the same time, the nanofiller coating further enhances the durability of the material, enabling the bag body to maintain stable strength during long-term immersion. However, due to the lack of composite structure protection, the force distribution of comparative example 5 is uneven, and the cracking and tearing phenomena gradually intensify, eventually leading to overall rupture.
[0164] The contribution of the multilayer composite structure is fully reflected here. The dynamic response substrate can not only adjust the pore size when heated, but also relieve stress concentration. The molecular sieve layer not only optimizes the internal structure distribution, but also shares part of the thermal stress, playing a role in stabilizing the overall performance. Without these synergistic effects, the single-layer membrane of Comparative Example 5 will inevitably lose strength and integrity rapidly at high temperatures.
[0165] The addition of nanofillers showed more detailed value in the experiment. Zinc oxide improves the high-temperature fatigue resistance of the material by combining with the substrate, while graphene oxide provides additional mechanical strength. Combined with the overall mechanism, Example 4 not only improves the durability of the bag body in practical applications, but also provides reliable protection for the high-temperature use of the filter bag in various scenarios. The results of Comparative Example 5 clearly show that the traditional single-layer structure cannot adapt to the complex needs in high-temperature scenarios. This gap is also a direct reflection of technological innovation.
[0166] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A multifunctional filter bag for a tea-making machine, comprising a bag body (4), characterized in that: A tightening ring (1) is arranged on the upper part of the bag body (4), a drawstring (2) is arranged inside the tightening ring (1), and a plurality of evenly distributed filter holes (3) are provided on the bag body (4).
2. A multifunctional filter bag for a tea maker according to claim 1, characterized in that: Also includes the following components: The dynamic response substrate is composed of N-isopropylacrylamide and polyacrylic acid and is formed by cross-linking with a cross-linking agent; Molecular sieve functional units, including mesoporous silica and cyclodextrin derivatives; performance-enhancing nanofillers, including graphene oxide and zinc oxide nanoparticles; Among them, the thickness of the dynamic response substrate is 50-100µm, the thickness of the molecular sieve functional unit is 30-50µm, and the thickness of the performance-enhancing nanofiller is 20-30µm.
3. A multifunctional filter bag for a tea maker according to claim 2, characterized in that: The mass of the N-isopropylacrylamide accounts for 40% to 50% of the dynamic response substrate, and the mass of the polyacrylic acid accounts for 30% to 40% of the dynamic response substrate.
4. A multifunctional filter bag for a tea maker according to claim 2, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide, and its mass accounts for 2% to 5% of the dynamic response substrate.
5. The multifunctional filter bag for a tea maker according to claim 2, characterized in that: The pore size of the mesoporous silica in the molecular sieve functional unit is in the range of 2-4 nm, and the mass accounts for 3% to 5% of the molecular sieve functional unit.
6. A multifunctional filter bag for a tea maker according to claim 2, characterized in that: The cyclodextrin derivative is beta-cyclodextrin grafted with carboxyl groups, and its mass accounts for 2% to 4% of the molecular sieve functional unit.
7. A multifunctional filter bag for a tea maker according to claim 2, characterized in that: The mass of graphene oxide in the performance-enhancing nanofiller accounts for 1% to 2% of the performance-enhancing nanofiller, and the mass of zinc oxide nanoparticles accounts for 1% to 2% of the performance-enhancing nanofiller.
8. The multifunctional filter bag for a tea maker according to claim 2, characterized in that: The dynamic response substrate, the molecular sieve functional unit and the performance-enhancing nanofiller are composited through multiple coating processes, with the number of coatings being 2-3 times.
9. A multifunctional filter bag for a tea maker according to claim 2, characterized in that: The bag body of the filter bag is made of a composite film, which is cut into a size of 8 cm×12 cm by laser cutting and packaged by heat sealing technology, with a heat sealing temperature of 100-120° C. and a heat sealing time of 3 to 5 seconds.
10. The multifunctional filter bag for a tea maker according to claim 2, characterized in that: The three-layer structure of the composite membrane is: a dynamic response substrate layer, a molecular sieve functional unit layer and a performance-enhancing nanofiller layer.